The development of problem-based learning to increase problem solving ability on Social Arithmetic for class VII SMP - Trianingsih, Ervina; Khabibah, Siti; Masriyah, Masriyah (Universitas Malikussaleh, 2022)
This study is categorized as development research. Learning tools developed in this research are Lesson Plans (RPP), Student Worksheets (LKS), and Problem Solving Ability Test (TKPM). The learning tools are developed using a 4-D development model which consists of four stages, namely the define stage, the design stage, the develop stage, and the disseminate stage. Based on the results of descriptive analysis obtained that the learning tools developed good quality because it meets the valid criteria, practical and effective. Learning tools are said to be valid because all validators provide a minimum score of 3 for each aspect of the assessment on a scale of 1 - 4 and problem solving ability test it meets validity, reliability, and sensitive criteria. Learning tools are said to be practical because the ability teacher to manage learning shows both minimal categories and student activities categorized effectively. Learning tools are said to be effective because students 'responses to positive learning tools and learning activities categorized positive, classical completeness are achieved, and problem based learning to increase students' problem solving skills is achieved. Based on the descriptive analysis in the implementation class, it was found problem based learning on social arithmetic material was effective for increase students' problem solving skills.